Implementasi Supervisi Akademik oleh Badan Koordinasi Lembaga Pendidikan Qur’an - Jariyah, Jariyah; Chusniyah, Atin; Rifa’i, Andi Arif (FONDATIA, 2023)
This study aims to (1) determine the implementation of academic supervision by the Qur’an Education Institution Coordinating Board of Qur’an Education Park At-Taqwa Karang Dawung Semarang, and (2) identify obstacles to the implementation of academic supervision the Qur’an Education Institution Coordinating Board of Qur’an Education Park At-Taqwa Karang Dawung Semarang. The research method used was qualitative case study method. Data collection techniques were conducted by interview, observation, and documentation. Data analysis techniques were data reduction, data presentation, and conclusion drawing/verification. The results showed that the implementation of academic supervision by the Qur’an Education Institution Coordinating Board based on aspects of planning, implementation, and follow-up can be categorized as not optimal. Factors that hinder the implementation of academic supervision in Qur’an Education Park include supervisors having external activities, supervisors not having supervision competence, and the commitment of Qur’an Education Park administrators to make improvements is still fluctuating.